Characterization of CrMoBW- Fe base in-flight particles and splats fabricated by nano cored wire arc spraying - Man Tuiprae (2018)
Properties and performance of the coating fabricated by wire arc spray process strongly depend on various factors including spray parameters and characteristics of both in-flight particle and splat. In this study, relationship between in-flight particle, splat formation and microstructure of the CrMoBW-Fe based nanocomposite coating fabricated by wire arc spray process were investigated. The Focus ion beam (FIB) milling was used to prepare a transversal cross-section of the in-flight particle and splat to be characterized by scanning electron microscopy (SEM) along with an energy dispersive x-ray spectroscopy (SEM-EDS). In addition, phase compositions were also analyzed by using x-ray diffractometer (XRD). The results revealed that size of the in-flight particles and splat morphology greatly influenced microstructure and properties of the coatings. In-flight particles were revealed a spherical-shape with a broad size distribution ranging from 0.8 to 115 μm at the average of 26 μm particle diameter. In-flight particles were well flattened on impact giving flower-shape splat with the average diameter of 100 μm. Flattening degree was found to be 3.8. Arc sprayed CrMoBW-Fe base nanocomposite coating showed very thin splat with fine lamella structure which implied that particles were fully molten upon impact onto substrate.